Development of Android Application Based Wrestling Learning Media in Covid-19 Pademic - Tatang Iskandar; Margono (Program Pascasarjana Universitas Negeri Jakarta, 2021)
Wrestling is one of the subjects taught at the Islamic University 45 Bekasi. The impact of the covid-19 pandemic made wrestling learning carried out online. In the modern era where technology is developing rapidly, the use of technology-based teaching materials continues to be developed so that the teaching and learning process is no longer dependent on the same place, paper or blackboard. The method used in this study was Research and Development with ADDIE development model, which refers to Analysis, Design, Development, Implementation, and Evaluation. The result of the development is in the form of wrestling learning material which is presented in an android application.